Impact of salinity stress on germination of water spinach (Ipomoea aquatica) - Ibrahim, Mohd Hafiz; Abas, Nur Azira; Zahra, Syeda Maasooma (Sciencedomain International, 2019)
Aims: Salinity is one of the major abiotic stress that negatively affects plant growth in germination and early seedling stages. Salinity has becoming a serious problem as most of the parts of worldwide lands were affected by high salt concentration. Therefore, the effects of salinity ranging from 0 mM, 25 mM, 50 mM and 75 mM Sodium chloride (NaCl) concentrations on germination and early seedling growth of water spinach and their salt tolerance mechanism. Study Design: Completely Randomized Design (CRD). Place and Duration of Study: This study was conducted at Tissue Culture Laboratory, Department of Biology, Faculty of Science in University Putra Malaysia (UPM) from June to August, 2018. Methodology: In order to study the effects of salinity on water spinach, several parameters have been taken into account for measurement which include water uptake percentage, germination percentage, germination index, mean germination time, relative injury rate, seed vigor, seedling height reduction, hypocotyl and radicle length, seedling biomass, salt tolerance, total phenolic content and total flavonoids contents. Results: The results obtained showed that salinity adversely reduced water uptake efficiency, seed vigor, hypocotyl and radicle length, total phenolic content and total flavonoids content of water spinach. The seedling height reduction of water spinach increased significantly in relative to increasing salinity. However, seeds treated in mild salt concentration at 25 mM of NaCl showed an increment of germination percentage and germination index. Conclusion: Salt tolerance of water spinach increased as the response towards increasing salinity. Results: The results obtained showed that salinity adversely reduced water uptake efficiency, seed vigor, hypocotyl and radicle length, total phenolic content and total flavonoids content of water spinach. The seedling height reduction of water spinach increased significantly in relative to increasing salinity. However, seeds treated in mild salt concentration at 25 mM of NaCl showed an increment of germination percentage and germination index. Conclusion: Salt tolerance of water spinach increased as the response towards increasing salinity.